2018
DOI: 10.1097/md.0000000000009060
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum 25-hydroxyvitamin D concentration and pulmonary infection in children

Abstract: We assessed the relationship between serum 25-hydroxyvitamin D (25(OH)D) level and community-acquired pneumonia (CAP) among Chinese children.This observational study examined children aged 3 days to 14 years (n = 1582) from the Capital Institute of Pediatrics in 2009 to 2011. There were 797 children in the CAP group and 785 controls. The CAP group was divided into 2 groups: a pneumonia group and pneumonia-induced sepsis group. The serum 25(OH)D level was estimated using micro whole blood chemiluminescence.The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 22 publications
4
31
0
Order By: Relevance
“…Since 1997, it has been shown in developing countries, where malnutrition and micronutrient deficiency were more common, that the incidence of pneumonia was higher in children with rickets [ 124 , 126 , 131 ], and treatment failure was seen more frequently in rachitic children [ 132 ]. Similar studies were conducted worldwide, evaluating the circulating levels of vitamin D in children with LRTI and in controls: several studies found that lower vitamin D levels were associated with higher risk of developing an acute respiratory tract infection [ 125 , 130 , 132 , 133 , 135 , 139 , 144 ], or were linked to a more severe course of illness [ 136 , 142 ], with more frequent need for oxygen supplementation, ventilation support [ 134 ], or increased risk of intensive care unit (ICU) admission and longer hospital stay [ 143 ].…”
Section: Vitamin Dmentioning
confidence: 83%
See 1 more Smart Citation
“…Since 1997, it has been shown in developing countries, where malnutrition and micronutrient deficiency were more common, that the incidence of pneumonia was higher in children with rickets [ 124 , 126 , 131 ], and treatment failure was seen more frequently in rachitic children [ 132 ]. Similar studies were conducted worldwide, evaluating the circulating levels of vitamin D in children with LRTI and in controls: several studies found that lower vitamin D levels were associated with higher risk of developing an acute respiratory tract infection [ 125 , 130 , 132 , 133 , 135 , 139 , 144 ], or were linked to a more severe course of illness [ 136 , 142 ], with more frequent need for oxygen supplementation, ventilation support [ 134 ], or increased risk of intensive care unit (ICU) admission and longer hospital stay [ 143 ].…”
Section: Vitamin Dmentioning
confidence: 83%
“…We searched PubMed using keywords such as “vitamin D” and “lower respiratory tract infections” or “viral infections,” focusing on studies on pediatric populations, including both observational studies and clinical trials. Numerous studies investigated the association between low levels of 25-hydroxyvitamin D and increased susceptibility to LRTI in childhood, as listed in Table 4 [ 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ].…”
Section: Vitamin Dmentioning
confidence: 99%
“…In particular, VD plays a prominent role in boosting innate immunity, regulating adaptive immunity, and strengthening airway mucosal responses. Previous epidemiological studies show consistent independent associations between lower circulating levels of 25‐hydroxyvitamin D (25(OH)D) during childhood and an increased risk of upper and lower RTIs, including tuberculosis, pneumonia, asthma exacerbations, and bronchiolitis . Moreover, data from a recent individual‐patient‐data meta‐analysis of clinical studies show that VD supplementation protects against acute respiratory infections .…”
Section: Introductionmentioning
confidence: 88%
“…It has been shown that vitamin D deficiency increases the susceptibility and hence the complications of infections [11][12][13][14]. A vitamin D level of less than 30 ng/mL is associated with different bacterial and viral infections [15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%